β-Sitosterol and Gemcitabine Exhibit Synergistic Anti-pancreatic Cancer Activity by Modulating Apoptosis and Inhibiting Epithelial–Mesenchymal Transition by Deactivating Akt/GSK-3β Signaling - Cao, Zhang-qi; Wang, Xue-xi; Lu, Li; Xu, Jing-wen; Li, Xiao-bin; Zhang, Guang-ru; Ma, Zhan-jun; Shi, An-chen; Wang, Yan; Song, Yu-jun (Frontiers in Pharmacology, 2019)
β-Sitosterol (BS), a major bioactive constituent present in plants, has shown potent anti-cancer activity against many human cancer cells, but its activity in pancreatic cancer (PC) cells has rarely been reported. Gemcitabine (GEM) is one of the first-line drugs for PC therapy, although the treatment effect is not sustained due to prolonged drug resistance. In this study, we firstly studied the anti-PC activity and the mechanism of BS alone and in combination with GEM in vitro and in vivo. BS effectively inhibited the growth of PC cell lines by inhibiting proliferation, inducing G0/G1 phase arrest and apoptosis, supressed the NF- kB activity, and increased expression of the protein Bax but decreased expression of the protein Bcl-2. Moreover, BS inhibited migration and invasion and downregulated epithelial–mesenchymal transition (EMT) markers and AKT/GSK-3β signalling pathways. Furthermore, the combination of BS and GEM exhibited a significant synergistic effect compared to that by BS or GEM alone in MIA-PaCa-2 and BXPC-3 cells. More importantly, the combination treatment with BS and GEM lead to significant growth inhibition of PC xenografts. Overall, our data revealed a promising treatment option for PC by the combination therapy of BS and GEM.